PENGARUH CAMPURAN SERAT KULIT PINANG DAN SERBUK GERGAJI TERHADAP KUAT TEKAN BATAKO - Winda Gustika Hami; Akbar Alfa; Rezky Kinanda (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2021)
There are various ways to improve the quality of bricks, based the amount of betel husk fiber waste and sawdust in the Indragiri Hilir area, the author is interested in examining the characteristics of bricks with additives ingredients of areca nut fiber and sawdust in terms of compressive strength. The bricks made were the solid bricks with a size of 39 cm x 9 cm x 10 cm as many as 4 samples, and each sample consisted of 5 test objects. The test used a variety of different additives, namely BSS 0 without the addition of additive ingredients, BSS 1 with 5% betel nut fiber added and 2% sawdust, BSS 2 with 3% betel nut fiber added and 1% sawdust, BSS 3 with added ingredients of 1% areca nut fiber and 4% sawdust. The compressive strength test was carried out at the age of 7 days and then converted to the age of 28 days. The average compressive strength of bricks at the age of 7 days with sample codes BSS 1 20.50 kg/cm2, BSS 1 16.85, BSS 2 8.11 kg/cm2, and BSS 3 2.14 kg/cm2 . There is a positive effect of the addition of betel nut and sawdust fiber on the compressive strength of the brick are y = 17.34 + 0.57 X1 + (-3.84 X2), coefficient of multiple determination (r2) is 0.86%, and the multiple correlation coefficient (r) is 0.93. Berbagai macam cara untuk meningkatkan kualitas dan mutu batako, melihat banyaknya limbah serat kulit pinang dan serbuk gergaji didaerah Indragiri Hilir, penulis tertarik untuk meneliti karakteristik batako dengan bahan tambah serat kulit pinang dan serbuk gergaji ditinjau dari kuat tekannya. Batako yang dibuat adalah batako pejal dengan ukuran 39 cm x 9 cm x 10 cm sebanyak 4 sampel, dan tiap sampel terdiri dari 5 buah benda uji. Pengujian menggunakan variasi campuran bahan tambah yang berbeda, yaitu BSS 0 tanpa penambahan bahan tambah, BSS 1 dengan bahan tambah serat kulit pinang 5% dan serbuk gergaji 2%, BSS 2 dengan bahan tambah serat kulit pinang 3% dan serbuk gergaji 1%, BSS 3 dengan bahan tambah serat kulit pinang 1% dan serbuk gergaji 4%. Pengujian kuat tekan dilakukan pada umur 7 hari kemudian dikonversikan ke umur 28 hari. Kuat tekan rata-rata batako pada umur 7 hari dengan kode sampel BSS 1 20,50 kg/cm2, BSS 1 16,85, BSS 2 8,11 kg/cm2, dan BSS 3 2,14 kg/cm2. Ada pengaruh positif penambahan serat kulit pinang dan serbuk gergaji terhadap kuat tekan batako yaitu y = 17,34 + 0,57 X1 + (-3,84 X2), koefisien determinasi ganda (r2) sebesar 0,86%, dan koefisien korelasi ganda (r) sebesar 0,93.